2020
DOI: 10.1093/ecco-jcc/jjz203.489
|View full text |Cite
|
Sign up to set email alerts
|

P360 Safety and clinical efficacy of double switch from originator infliximab to biosimilars CT-P13 and SB2 in patients with inflammatory bowel diseases (SCESICS): A multicentre study

Abstract: Background Since infliximab (IFX) patent expiry in 2015, several IFX biosimilars have been licensed in EU for all indications, including inflammatory bowel diseases (IBD). IFX biosimilars currently available in Italy include CT-P13 and SB2, both of which demonstrated comparable efficacy, safety and immunogenicity with IFX originator in IBD patients. Safety and clinical efficacy of single switch from originator IFX to CT-P13 have also been confirmed in a prospective clinical trial. On the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…However, very limited data are available with respect to switching between biosimilars in IBD with either long‐term outcomes or drug levels lacking 17,33,34 . We have shown that biosimilar‐to‐biosimilar switching does not have a negative influence in terms of infliximab trough levels and disease activity.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, very limited data are available with respect to switching between biosimilars in IBD with either long‐term outcomes or drug levels lacking 17,33,34 . We have shown that biosimilar‐to‐biosimilar switching does not have a negative influence in terms of infliximab trough levels and disease activity.…”
Section: Discussionmentioning
confidence: 85%
“…In a prospective real‐world observational study of 174 IBD patients ‘reverse switching’ from CT‐P13 to the originator Remicade, a small proportion (n = 14, 8%) had prior exposure to Remicade; no significant difference in clinical or infliximab trough level outcomes was seen by 24 weeks, regardless of prior exposure 36 . A recent abstract reported equivalent safety and efficacy data to Week 48 between 52 double‐switched IBD patients (originator to CT‐P13 to SB2) and 66 single‐switched controls (originator to CT‐P13) 33 . Likewise, similar safety and efficacy data were reported at 1 year between 24 double‐switched patients (originator to CT‐P13 to SB2) and a heterogeneous group commencing SB2 who were either naïve to anti‐TNF, infliximab, or being switched from CT‐P13 or originator 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent French study performed in 140 patients with various IMIDs with a similar double switch, 132 (94.3%) were still treated with maintenance SB2 therapy at the end of the study 25 . Other observational studies of IBD and psoriasis have reported similar findings 22,26‐28 . Infliximab is an important immunogenic treatment, and the immunisation is responsible for a loss of response or an increase in adverse events.…”
Section: Discussionmentioning
confidence: 85%
“…25 Other observational studies of IBD and psoriasis have reported similar findings. 22,[26][27][28] Infliximab is an important immunogenic treatment, and the immunisation is responsible for a loss of response or an increase in adverse events. In our study, the rate of ADA did not increase after the switch (3.9% vs 2.8%, P = 0.75).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, overall, there are seven real-world studies reported in which patients switched from one biosimilar to another. These studies provide some initial and preliminary support for the safety and efficacy of cross-switching, although, overall, the study durations are relatively short, sample sizes are comparatively small, and the existing data are limited to evaluations of infliximab biosimilars [1,[121][122][123][124][125][126]. Nevertheless, it should be considered that several adalimumab biosimilars have now been approved and are on the market in the EU-and presumably switches among them have occurred as matter of practical reality, yet reports of harm associated with adalimumab biosimilar cross-switching are conspicuously scarce [127].…”
Section: Evidence Of the Safety And Efficacy Of Biosimilar Cross-switchingmentioning
confidence: 99%